Hearing loss in newborn infants with hypoxic ischaemic encephalopathy: protocol for a case–control study - Narendra Aladangady; Sujith Pereira; Milton D'costa (BMJ Paediatrics Open)
Introduction Hypoxic ischaemic encephalopathy (HIE), a condition where the brain does not receive enough oxygen and/or blood flow around the time of birth, is associated with significant morbidity and mortality. Systemic circulation may be affected due to poor myocardial function. The cochlear hair cells are vulnerable to changes in microcirculation, which may occur in HIE predisposing to hearing loss. Therefore, all infants with HIE undergo neurodevelopmental surveillance after discharge to monitor for adverse neurodevelopment including speech and hearing problems. This study will examine the incidence of confirmed hearing loss in newborn infants with any stage of HIE (cases) and compare them with controls.Methods and analysis All infants diagnosed with any stage of HIE (cases) over a 12-year period (January 2010 to December 2021) will be examined. Controls were newborn infants without HIE who were admitted to the neonatal unit and received intensive care including antibiotics (control group 1) and stable infants in the postnatal ward who received antibiotics (eg, gentamicin) (control group 2). Controls matched for gestation, gender and birth weight will be selected from a similar time period. Infant details and hearing screening data will be gathered from prospectively entered BadgerNet and S4H system databases, respectively. Categorical data will be analysed using the χ2 test. Predictors for hearing loss will be performed using binary logistic regression analysis.Ethics and dissemination The study is approved by the Health and Care Research Wales (HCRW) Research Ethics Committee and the Health Research Authority (HRA) (reference 21/HRA/4506). The study findings will be presented at national/international conferences and published in peer-reviewed scientific journals.